Comparação entre os orçamentos de uma edificação térrea de alto padrão em light steel frame e em concreto armado com alvenaria de vedação - Pereira, Lucas Henrique Souza (Universidade Federal de São Carlos, 2023)
The Brazilian construction of houses and buildings is mainly composed of reinforced concrete and masonry, which have a low degree of industrialization, thus generating waste and rework. The light steel frame (LSF) and wood frame (WF) construction systems change this reality, due to the high level of industrialization, for this and other reasons these systems are used on a large scale in several countries. As these construction systems are not widespread in Brazil, there is a lack of knowledge and misinformation, so the work carried out seeks to elucidate the characteristics of construction systems, through a bibliographic survey, drawing a comparison between the LSF and WF from the project phase and post-occupancy, showing the similarities and differences between the systems. In addition, it aims to prove the economic viability of such projects, therefore, a case study will be prepared, adopting as a parameter a high-end single-family residence built in concrete and masonry, this project will be adapted to the LSF and WF systems, to do the precise material listing and budget. For the case study carried out, the total cost of services (considering materials and labor) was about 14% higher for the LSF system compared to the conventional solution, but this does not make the system unfeasible for those who seek a quick, efficient construction with zero waste. Specifically, in the foundation and superstructure stages, the conventional solution cost 80% and 11% higher than the LSF solution. However, in the closing stage (for the adopted methodology) the cost of the LSF solution was 71% higher than the conventional solution, mainly due to the use of high-performance and industrialized materials.
Comparison between the budgets of a high standard single storey building in light steel frame and in reinforced concrete with masonry
Keywords: Construção industrializada; Light steel frame; Wood frame; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL; ENGENHARIAS::ENGENHARIA CIVIL::ESTRUTURAS